2′-O-ribose methylation levels of ribosomal RNA distinguish different types of growth arrest in human dermal fibroblasts - Yang, Guohuan; Schmid-Siegel, Maximilian; Heissenberger, Clemens; Koš-Braun, Isabelle C.; Prechtl, Martina; Meca-Laguna, Gabriel; Rocha, Marta; Wagner-Schrittwieser, Anja; Pils, Vera; Meixner, Barbara; Tav, Koray; Hengstschläger, Markus; et al. (Journal of cell science, 2024)
The 2′-O-methylation (2′-O-Me) of ribosomal RNA (rRNA) shows plasticity that is potentially associated with cell phenotypes. We used RiboMeth-seq profiling to reveal growth arrest-specific 2′-O-Me patterns in primary human dermal fibroblasts from three different donors. We exposed cells to hydrogen peroxide to induce cellular senescence and to high cell densities to promote quiescence by contact inhibition. We compared both modes of cell cycle arrest to proliferating cells and could indeed distinguish these conditions by their overall 2′-O-Me patterns. Methylation levels at a small fraction of sites showed plasticity and correlated with the expression of specific small nucleolar RNAs (snoRNAs) but not with expression of fibrillarin. Moreover, we observed subtle senescence-associated alterations in ribosome biogenesis. Knockdown of the snoRNA SNORD87, which acts as a guide for modification of a hypermethylated position in non-proliferating cells, was sufficient to boost cell proliferation. Conversely, depletion of SNORD88A, SNORD88B and SNORD88C, which act as guides for modification of a hypomethylated site, caused decreased proliferation without affecting global protein synthesis or apoptosis. Taken together, our findings provide evidence that rRNA modifications can be used to distinguish and potentially influence specific growth phenotypes of primary cells.
Veröffentlicht: 12. Februar 2024
Gesehen am 21.08.2024